EXACERBATED ECZEMA: ROLE OF BUILT ENVIRONMENT IN INCREASING DISEASE SEVERITY AMONG PAKISTANI PATIENTS - Bisma Laeeque; Muhammad Laeeque; Zirgham Masood; Muhammad Ijaz Ahmed (ziauddin University, 2019)
Atopic Eczema is a non-contagious skin disease. This study was undertaken to determine the role of home environment allergens in aggravation of atopic eczema by using EASI (Eczema Area And Severity Index) and POEM (Patient Oriented Eczema Measure). Furthermore statistical analysis was conducted to ascertain contribution of indoor environment allergen in exacerbating disease severity among male and female patients in Pakistan. The results revealed that home environment allergens have the potential to increase severity of atopic eczema experienced by the patients. Paints, air quality and fabric coverings were the most eczema deteriorating elements found inside Pakistani homes.